Distributional shifts in ectomycorrizhal fungal communities lag behind climate-driven tree upward migration in a conifer forest-high elevation shrubland ecotone. (October 2019) - Álvarez-Garrido, Lucía; Viñegla, Benjamín; Hortal, Sara; Powell, Jeff R.; Carreira, José A.
Abstract: Increasing temperatures are leading to upward migration of plant species in mountains, with elevational shifts of the mountain tree-line being the most commonly documented response ("front-edge" of altitudinal advance). Rapid distributional and compositional shifts in soil microbial communities, especially ectomycorrhizal (ECM) fungi, under climate change are also expected as an indirect effect of the impacts on vegetation. However, and despite the potential consequences on ecosystem functioning, they have seldom been addressed. Here we test the hypothesis that distributional shifts in soil ECM fungal communities will follow climate-driven tree upward migration in a fir forest-high elevation shrubland ecotone. Using Illumina Miseq sequencing, we compare the ECM fungal community associated to roots of adult Abies pinsapo trees at the tree-line with that of individuals involved in the altitudinal advance above it. Our data showed a decreasing trend in ECM fungal species abundance, richness, and proportion of species with epigeous fruiting bodies toward higher altitudes above the tree-line. Agaricales, Boletales and Pezizales were the fungal orders most frequently shared between host-individuals from the tree-line and the upward-migration area. In the latter, the ECM fungal community was mainly affected by the distance from the tree-line. Our results, together with the fact that the tree upward-migration process began several decades ago, suggest that (i) there is a high host-symbiont specificity for the ECM fungal community associated with the relic species Abies pinsapo, (ii) the altitudinal shift in the ECM fungal community lags well behind climate-driven tree upward migration in this forest-high elevation shrubland ecotone, and (iii) ECM dispersal limitation (distance from the forest-edge source) is an important factor controlling the speed of ECM upward migration. Highlights: Abies pinsapo upward migration results in spatial asynchrony with ECM fungi. ECM fungi do not keep pace with even moderate host-tree altitudinal migration rates. ECM fungal diversity decreased with distance and altitude from the tree-line. High host-specificity and dispersal limitation likely limit ECM upward migration.